Kantian Feeling: Empirical Psychology, Transcendental Critique, and Phenomenology - Frierson, Patrick (Con-Textos Kantianos. International Journal of Philosophy, 2016)
This paper explores the relationship between empirical psychology, transcendental critique, and phenomenology in Kant’s discussion of respect for the moral law, particularly as that is found in the Critique of Practical Reason. I first offer an empirical-psychological reading of moral respect, in the context of which I distinguish transcendental and empirical perspectives on moral action and defend H. J. Paton’s claim that moral motivation can be seen from two points of view, where “from one point of view, [respect] is the cause of our action, but from another point of view the moral law is its ground.” Then, after a discussion of a distinction between first- and second-order transcendental/practical perspectives where reasons for action are first-order practical judgments while the conditions of possibility for those reasons’ authority are expressed in second-order judgments, I turn to a third kind of perspective: the properly phenomenological one. I explain the general notion of Kantian phenomenology with an example of the experience of time from Kant’s Anthropology before applying this to a phenomenological reading of the discussion of respect in the Critique of Practical Reason. I end by noting that on my account, in contrast to that of Jeanine Grenberg, the distinctive phenomenology of respect is not systematically important for grounding claims in moral philosophy.
Keywords: Kant; Phenomenology; Moral Feeling; Empirical Psychology